2004
DOI: 10.1021/ja045870l
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Macromers as in Situ Polymerizing Biomaterials for Securing Cataract Incisions

Abstract: Dendritic macromers are attractive macromolecules for hydrogel formation since high cross-linking densities at low polymer concentration can be obtained, varied physical properties can be observed based on the macromer structure, and low viscous aqueous solutions can be injected in an in vivo site of irregular shaped to form a well-integrated polymer network. A peptide dendron possessing terminal cysteine residues was synthesized and characterized. When this peptide dendron was mixed with poly(ethylene glycol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
135
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(135 citation statements)
references
References 22 publications
0
135
0
Order By: Relevance
“…They have also demonstrated the use of the dendritic bio adhesive ([G1]-PGLSA-MA) 2 -PEG in numerous ocular applications including central corneal lacerations [143], clear corneal cataract incisions [144,145], flaps from LASIK surgery [146], scleral incisions [147] and 8-mm penetrating keratoplasties [148]. These in vitro studies tested the capability of this sealant to withstand high IOP (mean leakage pressure of 78.7 mmHg in lacerated cornea) [149].…”
Section: Photo-activated Dendritic Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…They have also demonstrated the use of the dendritic bio adhesive ([G1]-PGLSA-MA) 2 -PEG in numerous ocular applications including central corneal lacerations [143], clear corneal cataract incisions [144,145], flaps from LASIK surgery [146], scleral incisions [147] and 8-mm penetrating keratoplasties [148]. These in vitro studies tested the capability of this sealant to withstand high IOP (mean leakage pressure of 78.7 mmHg in lacerated cornea) [149].…”
Section: Photo-activated Dendritic Polymersmentioning
confidence: 99%
“…One such adhesive developed consists of lysine-based peptide dendrons with N-terminal cysteine conjugates that react with poly-(ethylene glycol dialdehyde). This formulation was successfully applied for the repair of 3 mm clear corneal incisions [145] and sealing of LASIK flap edges [150] in enucleated eyes.…”
Section: Chemical CXL (Two-component) Dendritic Polymersmentioning
confidence: 99%
“…Recently, this reaction was explored by Grinstaff et al for the preparation of in-situ forming hydrogels due to the mild chemical reaction conditions. A typical peptide ligation reaction is based on the reaction of aldehyde groups in poly(ethylene glycol) derivatives and NH 2 -terminal cysteine moieties in peptide dendrons, which can form thiazolidine rings (Wathier et al, 2004) (Fig.4a). The gelation process took place within a few minutes.…”
Section: Peptide Ligationmentioning
confidence: 99%
“…We have found that crosslinkable derivatives of these dendrimers are useful for the repair of ophthalmic wounds and articular cartilage (35,37,(40)(41)(42). Recently, we described the encapsulation characteristics of a poly(glycerol-succinic acid) (PGLSA) dendrimer and the use of this macromolecule as a potential vehicle for drug delivery (43).…”
Section: Introductionmentioning
confidence: 99%